Overexpression of endothelial nitric oxide synthase prevents diet-induced obesity and regulates adipocyte phenotype - Sansbury, Brian E; Cummins, Timothy D; Tang, Yunan; Hellmann, Jason; Holden, Candice R; Harbeson, Matthew A; Chen, Yang; Patel, Rakesh P; Spite, Matthew; Bhatnagar, Aruni; Hill, Bradford G (Circulation research, 2012)
Endothelial dysfunction is a characteristic feature of diabetes and obesity in animal models and humans. Deficits in nitric oxide production by endothelial nitric oxide synthase (eNOS) are associated with insulin resistance, which is exacerbated by high-fat diet. Nevertheless, the metabolic effects of increasing eNOS levels have not been studied. The current study was designed to test whether overexpression of eNOS would prevent diet-induced obesity and insulin resistance. In db/db mice and in high-fat diet-fed wild-type C57BL/6J mice, the abundance of eNOS protein in adipose tissue was decreased without significant changes in eNOS levels in skeletal muscle or aorta. Mice overexpressing eNOS (eNOS transgenic mice) were resistant to diet-induced obesity and hyperinsulinemia, although systemic glucose intolerance remained largely unaffected. In comparison with wild-type mice, high-fat diet-fed eNOS transgenic mice displayed a higher metabolic rate and attenuated hypertrophy of white adipocytes. Overexpression of eNOS did not affect food consumption or diet-induced changes in plasma cholesterol or leptin levels, yet plasma triglycerides and fatty acids were decreased. Metabolomic analysis of adipose tissue indicated that eNOS overexpression primarily affected amino acid and lipid metabolism; subpathway analysis suggested changes in fatty acid oxidation. In agreement with these findings, adipose tissue from eNOS transgenic mice showed higher levels of PPAR-α and PPAR-γ gene expression, elevated abundance of mitochondrial proteins, and a higher rate of oxygen consumption. These findings demonstrate that increased eNOS activity prevents the obesogenic effects of high-fat diet without affecting systemic insulin resistance, in part, by stimulating metabolic activity in adipose tissue.